English and psychiatry - Kelsey O’Connell (Mental Illness)
The writers who capture the minds and ears of the psychiatric community have a variety of motivations. They could want you to endorse a drug, a diagnosis, or a theory. In their efforts to persuade you, they will use rhetorical strategies. Rhetorical strategies are methods of writing to persuade a reader of an over-arching conclusion. With training in these strategies, it becomes easier for members of all disciplines, including psychiatry, to understand what methods of persuasion are being used on them.